Pre-service teachers' readiness on the teaching of arabic language : a case study at Universiti Pendidikan Sultan Idris - Nor Khalila binti Azizan (Kulliyyah of Education, International Islamic University Malaysia, 2015)
The teaching process is highlighted as a crucial issue since the main goal of teaching must be guaranteed effective. Having ready before teaching is not an exception in this regard as the teacher's criteria in imparting knowledge to his students is expectedly intended to facilitate effective and meaningful teaching. Therefore, the study generally attempts to investigate the perceived level of pre-service teachers' readiness towards teaching Arabic language. The study attempted to determine the level of readiness in three areas; Knowledge of Subject Area (KSA), Pedagogical Content Knowledge (PCK) and Interest in the teaching of Arabic language. The present study also attempted to verify the association between KSA and Interest and KSA and PCK. The study employed a survey method to gather the data. The respondents of this study were final year of pre-service teachers of Bachelor Degree Arabic Language with Education at Sultan Idris University of Education. The study used a set of questionnaire as an instrument to collect the data. It was distributed to thirty (30) respondents and the data collected were analyzed using Statistical Package for Social Science (SPSS 17.0) software. The simple descriptive statistical analysis; percentage, frequency, standard deviation and mean was used to interpret the data. Besides that, the inferential statistical analysis; chi-square test were used to examine the association between the variables. The findings show that the readiness in terms of KSA and PCK among pre-service teachers was at a medium level. Meanwhile, the result demonstrates a high level of interest in the teaching of Arabic language among pre-service teachers. The results of findings also identified that there is no association between KSA and Interest in the teaching of Arabic language among population. In the meantime, the study shows that there is strong association between KSA and PCK among pre-service teachers on the teaching of Arabic language. The study recommends some recommendations to further improve the performance of Bachelor Degree Arabic Language with Education pre-service teachers to enhance the level of readiness during teaching training period. At the same time, it is hoped that the study could assist and benefit the stakeholder of schools such as the curriculum planners and the faculty of education in universities to design more comprehensive and cohesive curriculum in the future in order to prepare Arabic language pre-service teachers better in the teaching profession.